UJI AKTIVITAS ANTIOKSIDAN MENGGUNAKAN RADIKAL 1,1-DIFENIL-2-PIKRILHIDRAZIL (DPPH) DAN PENETAPAN KANDUNGAN FENOLIK TOTAL FRAKSI ETIL ASETAT EKSTRAK ETANOLIK DAUN BENALU (Dendrophthoe pentandra L. Miq.) YANG TUMBUH DI POHON KEPEL (Stelechocarpus burahol (Bl.) Hook. f.) - Willigis Danu Patria; C.J. Soegihardjo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: Antioxidant has the ability to capture free radicals. These free radicals can oxidizenucleic acids, proteins, lipids or DNA, causing degenerative diseases. Antioxidants compoundfound in plants such as phenolic acids, polyphenols and flavanoids would capture free radicalssuch as peroxide, hydroperoxide or lipid peroxyl and also inhibit the oxidative mechanisms thatshow degenerative diseases. Quercetin and quercetin 3-o-rhamnosida as constituents ofmistletoes (Dendrophthoe pentandra (L.) Miq.), are able to provide antioxidant activity.Mistletoes dried and extracted with 70% ethanol, followed by fractionation with ethyl acetate.Antioxidant activity of ethyl acetate fraction from ethanol extract was calculated using DPPHmethod and obtained IC50 values. The results showed that the ethyl acetate fraction fromethanolic mistletoes leaf extract has antioxidant activity with IC50 value of (12.57 0.7) mg / mL.The content of total phenolic (13.760.9) mg gallic acid equivalents per gram of ethyl acetatefraction from ethanol extract of leaves of the mistletoes.Keywords: Antioxidant, misletoes leaf, Dendrophthoe pentandra, ethyl acetate fraction,ethanolic extract, DPPH, total phenolic..